Enhanced Generation of Induced Cardiomyocytes Using a Small‐Molecule Cocktail to Overcome Barriers to Cardiac Cellular Reprogramming. Issue 12 (16th June 2020) - Singh, Vivek P.; Pinnamaneni, Jaya Pratap; Pugazenthi, Aarthi; Sanagasetti, Deepthi; Mathison, Megumi; Wang, Kai; Yang, Jianchang; Rosengart, Todd K.
Abstract : Background: Given known inefficiencies in reprogramming of fibroblasts into mature induced cardiomyocytes (iCMs), we sought to identify small molecules that would overcome these barriers to cardiac cell transdifferentiation. Methods and Results: We screened alternative combinations of compounds known to impact cell reprogramming using morphologic and functional cell differentiation assays in vitro. After screening 6 putative reprogramming factors, we found that a combination of the histone deacetylase inhibitor sodium butyrate, the WNT inhibitor ICG‐001, and the cardiac growth regulator retinoic acid (RA) maximally enhanced iCM generation from primary rat cardiac fibroblasts when combined with administration of the cardiodifferentiating transcription factors Gata4, Mef2C, and Tbx5 (GMT) compared with GMT administration alone (23±1.5% versus 3.3±0.2%; P <0.0001). Expression of the cardiac markers cardiac troponin T, Myh6, and Nkx2.5 was upregulated as early as 10 days after GMT–sodium butyrate, ICG‐001, and RA treatment. Human iCM generation was likewise enhanced when administration of the human cardiac reprogramming factors GMT, Hand2, and Myocardin plus miR‐590 was combined with sodium butyrate, ICG‐001, and RA compared with GMT, Hand2, and Myocardin plus miR‐590 treatment alone (25±1.3% versus 5.7±0.4%; P <0.0001). Rat and human iCMs also more frequently demonstrated spontaneous beating in coculture with neonatal cardiomyocytes with the addition of sodium butyrate, ICG‐001, and RA to transcription factor cocktails compared with transcription factor treatment alone. Conclusions: The combined administration of histone deacetylase and WNT inhibitors with RA enhances rat and human iCM generation induced by transcription factor administration alone. These findings suggest opportunities for improved translational approaches for cardiac regeneration.